An Analysis of Pragmatics Study in the Film of Tarung Sarung 2020 by Archie Hekagery - Uswatunnisa (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2022)
Departing from the view that meaning, language, and communication cannot be separated in everyday life, the result of this research is an analysis of the pragmatics in conversation and context depicted in the film